Dinamika Sosial-Ekonomi: Pertambangan Tradisional dan Ketahanan Masyarakat di Kalimantan Selatan: Socio-Economic Dynamics: Traditional Mining and Community Resilience in South Kalimantan - Jumriani Jumriani; Rochgiyanti Rochgiyanti; Blackson Kanukisya (Society, 2023)
Indonesia has abundant natural resources, including valuable diamonds, greatly impacting its mining industry, economy, and other environmental and societal sectors. This research, conducted in Sungai Tiung Village, Cempaka Sub-district, Banjarbaru City, South Kalimantan Province, Indonesia, explores how the use of natural resources, economic activities, and community resilience are interconnected by examining the enduring traditional mining practices in South Kalimantan, focusing specifically on diamond panning. Using qualitative research methods, this research collected comprehensive data through observations, interviews, and documentation involving key stakeholders such as miners, local communities, and government representatives. The analysis, which incorporates triangulation and expanded observations, reveals three key aspects of traditional mining patterns: the equipment used, the complexities of the work system, and how mining outcomes are shared. The findings highlight the resilience embedded in the traditional mining practices of diamond prospectors in South Kalimantan, showing how these practices influence work methods and reflect traditional community life, characterized by a cooperative and tolerant approach. As a result, this research deepens our understanding of diamond panning. It provides valuable insights into the relationship between traditional practices and the resilience of local communities on a broader scale.